Asphalt modifier and modified colored asphalt
By performing multi-step surface modification and composite modification of nano silica, the problem of uneven dispersion in asphalt is solved, and the low-temperature performance and anti-aging properties of modified colored asphalt are significantly improved.
Patent Information
- Application Number
- CN202311018999.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-14
AI Technical Summary
The prior art is difficult to achieve uniform dispersion of nanomaterials in asphalt, resulting in poor low-temperature performance and increased viscosity of modified asphalt.
By performing multi-step surface modification treatment of nanosilicon dioxide, including the use of strong alkalis, surfactants and silane coupling agents, reduce active groups and promote dispersion, followed by compound modification with stearic acid to increase steric resistance And prevent reunion.
The dispersion and compatibility of nanosilicon dioxide in asphalt is significantly improved, agglomeration is avoided, and the high and low temperature performance and anti-aging properties of modified colored asphalt are improved.
Abstract
Description
Technical Field
[0001] The invention discloses an asphalt modifier and modified colored asphalt, belonging to the technical field of compounds for asphalt modification. Background Art
[0002] Colored asphalt is a binder with the properties of petroleum asphalt, which is made of base oil, petroleum resin and modifier. Due to the large amount of low-viscosity base oil added to colored asphalt, the high-temperature performance of colored asphalt is poor, so additives are needed to improve the high-temperature performance of colored asphalt. Due to its unique properties, nanomaterials can significantly improve the high-temperature performance of modified asphalt by adding them to modified asphalt. Therefore, nanomaterials are often used as modifiers and are widely used in the field of modified asphalt.
[0003] The modification effect of nanomaterials is closely related to their dispersibility in the modified system. As inorganic materials, they have poor compatibility in asphalt, resulting in poor low-temperature performance of modified asphalt, which will have an adverse effect on the low-temperature performance of modified asphalt. This is because the surface of nanomaterials has a high number of active groups, which are prone to self-agglomeration, making it difficult for nanomaterials to be fully dispersed in asphalt. In addition, due to the formation of agglomeration points, they are prone to brittle fracture under the action of low temperature and external force, affecting the low-temperature performance of modified asphalt. Moreover, this agglomeration will also cause a significant increase in the viscosity of the prepared asphalt.
[0004] Patent CN116120838A discloses a root-penetration-resistant waterproof coating, preparation and construction, which discloses the use of a silane coupling agent to modify the surface of silica filler, but it mainly solves the asphalt anti-seepage or low-temperature spraying properties, and fails to effectively solve the problem of low-temperature brittle cracking of asphalt caused by agglomeration of the modifier. Patent CN202011258669.2 discloses a colored asphalt and a preparation method thereof, in which an alkali is used to modify the surface of silica, but the inventors found that after the surface of silica is modified with an alkali, its surface roughness increases, its activity increases, and it is more likely to agglomerate, which reduces the low-temperature performance of asphalt. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an asphalt modifier and modified colored asphalt with good dispersibility in asphalt.
[0006] The technical solution adopted by the present invention to solve the technical problem is: an asphalt modifier, characterized by comprising nano silicon dioxide whose surface is modified by a strong alkali solution, a surfactant solution, a hydrolysis solution of a silane coupling agent and a stearic acid solution in sequence.
[0007] Preferably, the surfactant is one or both of sodium alkylbenzene sulfonate and alkyl sulfonate, which are anionic emulsifiers, can be rapidly hydrolyzed under alkaline conditions, and are easily soluble in water, making them easy to clean and reducing the steps of subsequent treatment.
[0008] Preferably, the silane coupling agent is one or both of KH550 and KH570.
[0009] The present invention reduces the active groups with high energy on the surface of nano silicon dioxide by surface modification treatment of nano silicon dioxide. Sodium hydroxide is used to treat the surface of nano silicon dioxide to increase the roughness of the surface of nano silicon dioxide, thereby increasing its surface area, expanding the contact area with the silane coupling agent, and facilitating the complete subsequent grafting reaction; a surfactant is used, when the nano silicon dioxide treated with sodium hydroxide is added, the sodium hydroxide adsorbed on the surface of the nano silicon dioxide is dissolved in the surfactant solution, and the pH value of the surfactant solution is adjusted to alkaline, at which time the emulsification and dispersing properties of the surfactant are released, promoting the uniform dispersion of nano silicon dioxide particles, and at the same time, the surfactant adsorbed on the surface of the nano silicon dioxide carries an electric charge due to hydrolysis under alkaline conditions, increasing the mutual repulsion between the nano silicon dioxide particles, and preventing the agglomeration between the nano silicon dioxide particles.
[0010] Secondly, the uniformly dispersed nano-silica particle solution is mixed with the hydrolyzed solution of the silane coupling agent, and the organic groups generated after the hydrolysis of the silane coupling agent are used to undergo a grafting reaction with the active groups on the surface of the nano-silica particles, thereby reducing the content of active groups on the surface of the nano-silica particles, reducing the energy on the surface of the nano-silica particles, and preventing the agglomeration of the nano-silica particles. At the same time, the surface of the inorganic nano-silica particles is organically modified through the grafting reaction, which can increase the compatibility between the nano-silica particles and the petroleum resin.
[0011] Finally, long-chain stearic acid is used to perform composite modification on the silane-modified nano-silica particles. The long-chain stearic acid undergoes a secondary grafting reaction with the organic groups grafted on the nano-silica particles, which increases the length of the organic side chains and the steric hindrance between the nano-silica particles, further preventing the agglomeration of the nano-silica particles. In addition, stearic acid can further react with the unreacted active groups on the surface of the nano-silica particles, further reducing the energy on the surface of the nano-silica particles and preventing the agglomeration of the nano-silica particles.
[0012] Preferably, the surface modification comprises the following steps: 1) The strong alkaline solution is heated to 50-70°C and mixed with nano-silicon dioxide powder for surface modification, and the filter residue is obtained by filtration; 2) The surfactant solution is heated to 50-70° C., and mixed with the filter residue obtained in step 1) for 30-60 minutes to obtain a suspension; 3) The hydrolyzed solution of the silane coupling agent is heated to 70-80° C. and added to the suspension obtained in step 2), and the reaction is carried out for 150-200 min. The product is centrifuged, washed, and dried to obtain a solid; preferably, the drying temperature is 80° C. and the drying time is 60-80 min. 4) reacting the stearic acid solution with the solid obtained in step 3) at 60-80° C. for 180-240 min, centrifuging, washing and drying to obtain modified nano-silicon dioxide.
[0013] Preferably, the strong alkaline solution is obtained by mixing sodium hydroxide and water in a weight ratio of 0.1-0.5:1.
[0014] Stirring for 10 to 20 minutes at 50 to 70°C and a rotation speed of 100 to 200 rpm can accelerate the dissolution rate of sodium hydroxide in water. At the same time, within this concentration range, it is guaranteed that nano-SiO2 will react fully, while also ensuring that the reaction will not be insufficient due to low concentration of the strong alkali solution or excessive reaction due to high concentration.
[0015] Preferably, the surfactant solution is obtained by mixing water and a surfactant in a weight ratio of 94-95:5.
[0016] Preferably, the surfactant solution is obtained by mixing water, surfactant and thickener in a weight ratio of 94-95:5:0.05-0.1, and mixing at 300-500 rpm for 60-80 min. The preferred mixing speed is 300-500 rpm, and the mixing time is 60-80 min. The thickener first absorbs water and swells in the aqueous solution and then dissolves. Under this condition, the thickener can be quickly dissolved and dispersed; the use of a low speed can inhibit the foaming of the surfactant; and the uniformity of the thickener in the solution can be ensured. After adding the thickener, this step obtains a dispersed emulsion of nano-silicon dioxide.
[0017] Preferably, the thickener is one or both of anionic polyacrylamide and polyethylene glycol.
[0018] The addition of thickener increases the viscosity of the dispersed solution, allowing the nano-silica particles to be suspended in the solution, preventing the evenly dispersed nano-silica particles from secondary agglomeration, and further improving the dispersion of the nano-silica; the completely dispersed nano-silica particles are conducive to the complete grafting reaction in the next step.
[0019] Preferably, the hydrolysis solution of the silane coupling agent is a mixture of anhydrous ethanol and deionized water in a ratio of 2 to 4:1, 0.03 to 0.05 wt% of the silane coupling agent is added, and the mixture is mixed and reacted at 40 to 60° C. for 20 to 60 minutes to obtain the hydrolysis solution of the silane coupling agent. The preferred mixing reaction speed is 300 to 500 rpm.
[0020] Preferably, the stearic acid solution is obtained by mixing stearic acid and benzene solvent in a weight ratio of 0.1-0.3:1.
[0021] Further preferably, the benzene solvent is xylene. Xylene has a low boiling point and can be discharged as the temperature rises in the subsequent preparation process, reducing the impact of xylene on subsequent reactions.
[0022] A modified colored asphalt, characterized in that the raw materials include 50-68 parts of petroleum resin, 24-36 parts of base oil, 5-15 parts of polymer modifier SBR or SBS, and 1-5 parts of the above-mentioned asphalt modifier in parts by weight.
[0023] Preferably, the preparation method comprises the following steps: 1) Stir the base oil and polymer modifier according to weight at 130-160℃ for 10-30min, add asphalt modifier and mix evenly; 2) Add petroleum resin and dissolve it at 120-140℃ for 30-40min, then heat it to 140-150℃ and keep it at a constant temperature for 60-100min to obtain modified colored asphalt.
[0024] The polymer modifier is pre-mixed with the base oil. The polymer modifier absorbs the light components in the base oil and swells. The intertwined polymer chains are opened, which is conducive to the rapid formation of a three-dimensional network structure by the polymer modifier, and can better exert the modification effect. At the same time, since the amount of base oil added is higher than the amount of polymer modifier added, part of the base oil is in a flowing state, which reduces the viscosity of the system. At this time, adding modified nano-silica particles can reduce the dispersion resistance of the modified nano-silica particles and promote the uniform dispersion of the modified nano-silica particles; after the surface modification of the modified nano-silica particles, the compatibility between the modified nano-silica particles and organic substances is improved, which is beneficial to promote the dispersion of the modified nano-silica particles in the matrix asphalt; a large number of organic long chains are grafted on the surface of the surface-modified nano-silica particles, which can be entangled with the three-dimensional network structure of the polymer modifier, preventing the self-aggregation of the modified nano-silica particles, thereby solving the problem of the modified colored asphalt having a decreased low-temperature performance and a significant increase in viscosity due to the self-aggregation of the nano-silica particles. At the same time, this limiting effect reacts on the three-dimensional network structure of the polymer modifier, reducing the fluidity of the colored asphalt at high temperature, thereby improving the high-temperature performance of the colored asphalt. The modified nano-silica particles that have been evenly dispersed can play a lubricating role under the action of external shear force, thereby reducing the rotational viscosity of the colored asphalt. In addition, due to the even dispersion of the modified nano-silica particles, the anti-aging performance of the colored asphalt is greatly improved.
[0025] As a tackifier, petroleum resin has good compatibility with base oil. When added to the modified system, it can be quickly dissolved in the base oil, thereby increasing the viscosity of the modified system, thereby limiting the self-aggregation of the modified nano-silicon dioxide particles and improving the dispersibility of the modified nano-silicon dioxide particles. At the same time, as a high softening point component, petroleum resin can improve the high-temperature performance of the colored asphalt when added to the colored asphalt. Therefore, the above multiple components work together to improve the dispersibility of the modified nano-silicon dioxide particles, thereby improving the high and low temperature performance of the colored asphalt.
[0026] Preferably, the petroleum resin is a mixture of one or more of coumarone resin, terpene resin, fully hydrogenated petroleum resin and semi-hydrogenated petroleum resin in any proportion.
[0027] Preferably, the base oil is a mixture of one or more of cycloparaffinic oil, low aromatic oil, furfural extracted oil, and high aromatic oil in any proportion, and has a flash point of >230°C and a kinematic viscosity of less than 50 Pa·s at 40°C.
[0028] Preferably, the polymer modifier SBR is a pellet with a styrene content of 22.5-24.5% and a tensile strength of ≥15.0 MPa.
[0029] Preferably, the polymer modifier SBS has an S / B (weight ratio) of 30 / 70 and a melt flow rate (g•10 min -1 )0.1~5.
[0030] Compared with the prior art, the beneficial effects of the present invention are: significantly improving the dispersibility of inorganic nano-modifiers in asphalt, the nano-modifiers have good compatibility with asphalt, are evenly dispersed, have no agglomeration, have no low-temperature brittleness, limit high-temperature fluidity, and improve the high and low temperature performance of colored asphalt. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the examples. Example 2 is the best example of the present invention. In the following examples and comparative examples, nano-silicon dioxide and stearic acid are commercially available products; the polymer modifier SBS is SBS produced by Sinopec Baling Branch: S / B (weight ratio) 30 / 70, melt flow rate (g•10 min -1 ) 0.1~5; polymer modifier SBR is a commercially available product with a styrene content of 22.5~24% and a tensile strength of ≥15.0 MPa; the flash point of the base oil is >230℃, and the kinematic viscosity at 40℃ is less than 50Pa·s.
[0032] Example 1 An asphalt modifier, the preparation method comprises the following steps: 1) Sodium hydroxide and deionized water are mixed in a weight ratio of 0.3:1 to obtain a sodium hydroxide solution, which is heated to 60°C. Nano-SiO2 powder is added under stirring, and the alkali-treated nano-SiO2 powder is obtained after filtration.
[0033] 2) Deionized water, sodium alkylbenzene sulfonate and polyacrylamide are mixed in a weight ratio of 95:5:0.05 to obtain a sodium benzene sulfonate solution, which is mixed at 60°C and a stirring speed of 400 rpm for 60 to 80 minutes, and then the alkali-treated nano-SiO2 powder is slowly added, and stirring is continued for 30 to 60 minutes to obtain a nano-SiO2 dispersed emulsion.
[0034] 3) Anhydrous ethanol and deionized water were mixed in a weight ratio of 3:1, and silane coupling agent KH550 was slowly added. The mixture was reacted at 50°C and a stirring speed of 400 rpm for 20 minutes to obtain a silane coupling agent hydrolysis solution. The temperature was raised to 75°C, and the nano-SiO2 dispersion was slowly added. The reaction was continued for 150 minutes. The product was centrifuged, rinsed with ethanol, and placed in an oven at 80°C for constant temperature drying for 70 minutes to obtain silane coupling agent modified nano-SiO2.
[0035] 4) Stearic acid and xylene are mixed in a mass ratio of 0.2:1 to obtain a stearic acid solution, and then the nano-SiO2 modified by the silane coupling agent is uniformly dispersed therein under stirring conditions, and the reaction is carried out at a constant temperature of 70°C for 200 minutes. Centrifugation, washing, and drying are performed to obtain modified nano-SiO2, i.e., asphalt modifier.
[0036] A modified colored asphalt, the raw materials include 50 parts of petroleum resin, 36 parts of base oil, 11 parts of polymer modifier SBR, and 3 parts of asphalt modifier by weight. The petroleum resin is coumarone resin, and the base oil is naphthenic oil 4010.
[0037] The preparation method adopts the following steps: 1) Cycloalkane oil 4010 and polymer modifier SBR were kept in an oven at 135°C for 50 minutes according to weight, then reacted at 155°C and 1500 rpm for 20 minutes, and asphalt modifier was added and mixed for 40 minutes.
[0038] 2) After the coumarone resin is completely dissolved, react at 130°C for 35 minutes and place in an oven at 145°C for 75 minutes to obtain modified colored asphalt.
[0039] Example 2 A modified colored asphalt is prepared based on Example 1, wherein the raw materials are 53 parts of petroleum resin, 27 parts of base oil, 15 parts of SBR polymer, and 5 parts of asphalt modifier.
[0040] Other conditions are the same as in Example 1.
[0041] Example 3 A modified colored asphalt, based on Example 1, the petroleum resin is set to terpene resin, and the base oil is set to low aromatic oil G26.
[0042] Other conditions are the same as in Example 1.
[0043] Example 4 A modified colored asphalt is prepared based on Example 1, wherein the raw materials are 64 parts of petroleum resin, 26 parts of base oil, 8 parts of SBS polymer, and 2 parts of asphalt modifier.
[0044] Other conditions are the same as in Example 1.
[0045] Example 5 A modified colored asphalt is prepared based on Example 1, wherein the raw materials are 57 parts of petroleum resin, 30 parts of base oil, 10 parts of SBS polymer, and 3 parts of asphalt modifier.
[0046] Other conditions are the same as in Example 1.
[0047] Example 6 An asphalt modifier, based on Example 1, wherein the surface modifier is set to sodium alkyl sulfonate, the silane coupling agent is set to KH570, and in the preparation method thereof, in step 1), the weight ratio of sodium hydroxide to water is set to 0.5:1.
[0048] Other conditions are the same as in Example 1.
[0049] Example 7 An asphalt modifier is prepared in accordance with Example 1, wherein the weight ratio of deionized water to sodium alkylbenzene sulfonate and polyacrylamide in step 2) is set to 94:5:0.1, and the weight ratio of sodium hydroxide to water in step 1) is set to 0.1:1.
[0050] Other conditions are the same as in Example 1.
[0051] Comparative Example 1 A modified colored asphalt is provided. Based on Example 1, the asphalt modifier adopts nano silicon dioxide which has not been surface-modified.
[0052] Other conditions are the same as in Example 1.
[0053] Comparative Example 2 An asphalt modifier is disclosed. On the basis of Example 1, nano-SiO2 powder is treated in steps 1) and 2) of the preparation method thereof to obtain a nano-SiO2 dispersed emulsion, which is then filtered, washed with ethanol, and dried at 80°C to obtain the asphalt modifier.
[0054] Other conditions are the same as in Example 1.
[0055] Comparative Example 3 An asphalt modifier is prepared based on Example 1. The nano-SiO2 powder is not treated in steps 1) and 2) but directly treated in step 3) to obtain silane coupling agent-modified nano-SiO2 as an asphalt modifier.
[0056] Other conditions are the same as in Example 1.
[0057] Comparative Example 4 An asphalt modifier is disclosed. Based on Example 1, the preparation method of the asphalt modifier is to directly use step 4) to process the nano-SiO2 powder without using steps 1), 2), and 3) to obtain stearic acid-modified nano-SiO2 as an asphalt modifier.
[0058] Other conditions are the same as in Example 1.
[0059] Comparative Example 5 An asphalt modifier is prepared based on Example 1. The nano-SiO2 powder is not processed in steps 1) and 2) but directly processed in steps 3) and 4) to obtain silane coupling agent and stearic acid modified nano-SiO2 as an asphalt modifier.
[0060] Other conditions are the same as in Example 1.
[0061] Comparative Example 6 An asphalt modifier is disclosed. Based on Example 1, the preparation method of the nano-SiO2 powder does not use step 2) for treatment, but uses steps 1), 3), and 4) in sequence to obtain surface-modified nano-SiO2 as an asphalt modifier.
[0062] Other conditions are the same as in Example 1.
[0063] Comparative Example 7 An asphalt modifier is disclosed. Based on Example 1, the preparation method of the asphalt modifier is to use steps 2), 3), and 4) in sequence to obtain surface-modified nano-SiO2 as an asphalt modifier instead of using step 1).
[0064] Other conditions are the same as in Example 1.
[0065] Comparative Example 8 A modified colored asphalt, based on Example 1, is prepared by the following steps: 1) Add coumarone resin to cyclohexane oil 4010 by weight and dissolve it, and react for 35 minutes.
[0066] 2) Add polymer modifier SBR and keep it in an oven at a constant temperature of 135°C for 50 minutes, then react at 155°C and a stirring speed of 1500 rpm for 20 minutes, add asphalt modifier, mix for 40 minutes, and place it in an oven at a constant temperature of 145°C for 75 minutes to obtain modified colored asphalt.
[0067] Other conditions are the same as in Example 1.
[0068] Comparative Example 9 A modified colored asphalt, based on Example 1, is prepared by the following steps: 1) Cycloalkane oil 4010 and polymer modifier SBR were kept in an oven at 135°C for 50 minutes, then reacted at 155°C and 1500 rpm for 20 minutes. Under stirring, 2 parts of nano-silica powder and 2 parts of silane coupling agent were added in sequence and mixed for 40 minutes.
[0069] 2) After the coumarone resin is completely dissolved, react for 35 minutes and place in a 145°C oven for constant temperature development for 75 minutes to obtain modified colored asphalt.
[0070] Other conditions are the same as in Example 1.
[0071] Performance Testing The modified colored asphalt obtained in the above examples and comparative examples was subjected to performance tests, wherein the ductility test was determined according to the T0605-2011 method, the softening point test was determined according to the GB / T 4507-2010 method, the 135°C rotational viscosity was determined according to the T0625-2011 method, and the residual ductility ratio after aging was determined according to the SH / T 0736-2003 method. The test results are shown in Table 1 below.
[0072] Table 1 Performance test results .
[0073] By comparing the test results of the embodiments and the comparative examples, it can be seen that the modifier and modified colored asphalt prepared by the present invention and the preparation method thereof can solve the problem of a substantial decrease in the 5°C low-temperature ductility of the modified asphalt due to uneven dispersion and agglomeration of inorganic nano-SiO2 during the modification process by physically dispersing and grafting nano-SiO2, thereby improving the low-temperature performance of the nano-SiO2 modified asphalt; the modified SiO2 can significantly increase the softening point of the modified colored asphalt, and further enable the modified colored asphalt to maintain good low-temperature ductility after high-temperature aging, indicating that the modified nano-SiO2 can improve the high-temperature performance and anti-aging performance of the modified colored asphalt; at the same time, it is found that the modification treatment steps for nano-SiO2 in the present invention are coordinated and interrelated with each other, and jointly realize the modification of nano-SiO2, solving the problem of easy agglomeration of SiO2. In addition, Example 4 and Example 5 adopt SBS as modifier, SBS is the most commonly used polymer in modified asphalt at present, it is mainly based on improving the high temperature performance of asphalt, and takes into account the low temperature performance of asphalt, while SBR is mainly based on improving the low temperature performance of asphalt, taking into account the high temperature performance, and the test results show that the modified nano-SiO2 has good applicability. In addition, after the high and low temperature nano material is modified, it can prevent the inorganic nano material from causing the viscosity of the modified colored asphalt to increase significantly due to its own agglomeration. At the same time, it can be found by Comparative Examples 8 and Comparative Examples 9 that the addition order and preparation steps of each component in the patent of the present invention also have an interrelated effect. Therefore, there is a mutually coordinated, interrelated effect between the above-mentioned preparation steps and the preparation method in the patent of the present invention, and the performance of the modified colored asphalt is improved together.
[0074] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. An asphalt modifier, characterized in that: The invention comprises nano silicon dioxide which is surface-modified by a strong alkali solution, a surfactant solution, a hydrolysis solution of a silane coupling agent and a stearic acid solution in sequence.
2. The asphalt modifier according to claim 1, characterized in that: The surface modification comprises the following steps: 1) The strong alkaline solution is heated to 50-70°C and mixed with nano-silicon dioxide powder for surface modification to obtain filter residue; 2) The surfactant solution is heated to 50-70° C., and mixed with the filter residue obtained in step 1) for 30-60 minutes to obtain a suspension; 3) The hydrolyzed solution of the silane coupling agent is heated to 70-80° C. and added to the suspension obtained in step 2), and the reaction is carried out for 150-200 min. The product is centrifuged, washed, and dried to obtain a solid; 4) reacting the stearic acid solution with the solid obtained in step 3) at 60-80° C. for 180-240 min, centrifuging, washing and drying to obtain modified nano-silicon dioxide.
3. The asphalt modifier according to claim 1 or 2, characterized in that: The strong alkaline solution is obtained by mixing sodium hydroxide and water in a weight ratio of 0.1-0.5:
1.
4. The asphalt modifier according to claim 1 or 2, characterized in that: The surfactant solution is obtained by mixing water and the surfactant in a weight ratio of 94-95:
5.
5. The asphalt modifier according to claim 1 or 2, characterized in that: The surfactant solution is obtained by mixing water, a surfactant and a thickener in a weight ratio of 94-95:5:0.05-0.1 and mixing at 300-500 rpm for 60-80 minutes.
6. The asphalt modifier according to claim 1 or 2, characterized in that: The hydrolysis solution of the silane coupling agent is prepared by mixing anhydrous ethanol and deionized water in a ratio of 2 to 4:1, adding 0.03 to 0.05 wt% of the silane coupling agent into the mixed solvent, and mixing and reacting at 40 to 60° C. for 20 to 60 minutes to obtain the hydrolysis solution of the silane coupling agent.
7. The asphalt modifier according to claim 1 or 2, characterized in that: The stearic acid solution is obtained by mixing stearic acid and benzene solvent in a weight ratio of 0.1-0.3:
1.
8. The asphalt modifier according to claim 7, characterized in that: The benzene solvent is xylene.
9. A modified colored asphalt, characterized in that: The raw materials include 50-68 parts of petroleum resin, 24-36 parts of base oil, 5-15 parts of polymer modifier SBR or SBS, and 1-5 parts of the asphalt modifier described in any one of claims 1 to 7 by weight.
10. The modified colored asphalt according to claim 9, characterized in that: The preparation method comprises the following steps: 1) Stir the base oil and polymer modifier according to weight at 130-160℃ for 10-30min, add asphalt modifier and mix evenly; 2) Add petroleum resin and dissolve it at 120-140℃ for 30-40min, then heat it to 140-150℃ and keep it at a constant temperature for 60-100min to obtain modified colored asphalt.
Citation Information
Patent Citations
Root-puncture-resistant waterproof coating, preparation and construction
CN116120838A
Surface modification method of nanosilicon dioxide
CN103013182A
Stearic acid modified nano-silica adsorbing material and preparation method thereof
CN106334532A
Surface modification method of nano silica
CN107033629A
Colored asphalt and preparation method thereof
CN112876804A